Lion on the Hill - Meniru, Teresa E. (Macmillan Nigeria Publishers Ltd, 1991)
Ike, Musa and Toyin, all Junior Secondary class two boys of the Government College, Enugu, missed out of the national excursion to Kano because of their membership of the command performance. They later heard of Ike's uncle trauma in the hand of crooks wishing to steal his bronze artwork. Will the trio be able to bring the crooks to book?...
Keywords: Juvenile Fiction / Adventure